Wisata Ziarah Masjid Sayyid Arif Segopura sebagai Solusi Konseling Remaja Masjid Kota Pasuruan - Meilda Fitriana (Fakultas Dakwah IAIN Jember, 2022)
Pilgrimage can be a therapy, which consists of two words, namely therapy and pilgrimage. Therapy itself according to the Big Indonesian Dictionary (KBBI) is an attempt to restore the health of someone who is sick. Meanwhile, in Greek